Islamic Social Finance and Environmental Sustainability: A Study of Waqf-Driven Smart Waste Sorting and Recycling Solutions - Adamu Abubakar Muhammad; Shafa’at Ahmad Aliyu; Rabi Shehu Dalhatu; Huma Khan; Khadija Abdullahi (Civilization Research: Journal of Islamic Studies, 2026)
Solid waste management problems are getting worse in Muslim-majority communities due to rapid urbanization, poor funding, and a lack of technological integration.AI developments offer promising answers for recycling and garbage sorting, but their use is hampered by expenses and a lack of assistance. The function of waqf, or Islamic endowments, as a sustainable financing option consistent with Islamic principles is examined in this paper. It seeks to evaluate current waqf-funded environmental projects, determine whether AI in trash management is compatible with Islamic beliefs, and suggest a structure for "green waqf" financing to improve recycling programs. The study employs a qualitative and analytical research design, utilizing case study analysis of particular waqf-supported environmental projects, a survey of recent literature on Islamic social finance and environmental sustainability, and doctrinal examination of Islamic jurisprudential sources. Thematic content analysis is used to combine knowledge from policy reports, empirical investigations, and ancient Islamic texts that are pertinent to waste management, AI technologies, and waqf. The results show that waqf financing's sustainable framework, which encourages community involvement and strengthens environmental responsibility, can greatly enhance AI waste management. Legal changes for waqf investments in technology and capacity-building for waqf administrators are among the recommendations. By connecting waqf, artificial intelligence, and sustainable waste management, this study advances the area and emphasizes the importance of waqf in contemporary environmental solutions.